2022
DOI: 10.1038/s41539-022-00131-0
|View full text |Cite
|
Sign up to set email alerts
|

Instructor-learner body coupling reflects instruction and learning

Abstract: It is widely accepted that nonverbal communication is crucial for learning, but the exact functions of interpersonal coordination between instructors and learners remain unclear. Specifically, it is unknown what role instructional approaches play in the coupling of physical motion between instructors and learners, and crucially, how such instruction-mediated Body-to-Body Coupling (BtBC) might affect learning. We used a video-based, computer-vision Motion Energy Analysis (MEA) to quantify BtBC between learners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…An alternative claim, complement to the previous one, proposes that exogenous factors, referring to cues or influences outside the brain, such as movement synchrony (i.e., alignment in movements structure, direction, and pace) from an embodied perspective, also link to IBS, as inspired by recent takes (Shamay-Tsoory et al, 2019). Supporting the latter claim, our recent research has observed spontaneous movement synchrony and its association with learning outcome during learning interactions (Pan, Dikker, et al, 2022). Also, movement synchrony has been strongly linked to IBS in studies on social behavior (Koul et al, 2023b).…”
Section: Introductionmentioning
confidence: 69%
“…An alternative claim, complement to the previous one, proposes that exogenous factors, referring to cues or influences outside the brain, such as movement synchrony (i.e., alignment in movements structure, direction, and pace) from an embodied perspective, also link to IBS, as inspired by recent takes (Shamay-Tsoory et al, 2019). Supporting the latter claim, our recent research has observed spontaneous movement synchrony and its association with learning outcome during learning interactions (Pan, Dikker, et al, 2022). Also, movement synchrony has been strongly linked to IBS in studies on social behavior (Koul et al, 2023b).…”
Section: Introductionmentioning
confidence: 69%
“…We employed a grid search-based approach for hyperparameter optimization to determine the optimal regression parameters (i.e., C , γ , and ε ). A nested cross-validation method was implemented [ 65 ], with the outer leave-one-out cross validation (LOOCV) estimating the generalization performance of the model and inner 10-fold CV estimating and selecting the optimal hyperparameters. The prediction accuracy was estimated using the Pearson correlation coefficient between the predicted and actual values [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…Second, educators currently rely on single modal data for teaching and learning assessment, which overlooks important aspects of teaching such as nonverbal communication. To address this limitation, various multimodal technologies can be used to analyze teacher-student interactions, including EEG and fNIRS to observe changes in the cerebral cortex, eye tracking to monitor eye movements, skin conductance to examine physiological mechanisms, and video-based computer vision to detect teacher-student movement [79]. Such technologies enable a more comprehensive assessment of cognitive processes and neural responses during teacher-student interactions.…”
Section: Future Directionsmentioning
confidence: 99%